A Structural Model Approach to Leadership Style, Quality of Work Life and Communication Mediated by Motivation on Work Engagement (Empirical Study on the Ministry of Religious Affairs Work Unit in the South Papua Province Region)) - Paliman, Felisia Asri; Ratang, Westim; Wibowo, Martino (East Asian Journal of Multidisciplinary Research, 2024)
The demand to always have integrity, be professional, be responsible for work and the organization and be an example for others is not an easy matter for Civil Servants in the Ministry of Religion, especially in the South Papua Province region. This research aims to analyze the relationship between leadership style, quality of work life and communication mediated by motivation on employee work engagement. Data collection was carried out using a saturated sampling approach, with a final sample size of 148 respondents. The SEM analysis technique is carried out by evaluating the measurement model and structural model. The results of the analysis show that work motivation does not mediate the influence of leadership style, quality of work life and communication on employee engagement. It was found that there was a significant influence of leadership style, quality of work life and communication on work motivation, but these three variables had no effect on employee engagement.